THE CHANGE OF BRIDAL HAIR ACCESSORIES OF GREAT ACEH BRIDES - Aprilia Mentari; . Mukhirah; . Fitriana (Universitas Syiah Kuala, 2017)
Bridal hair accessories are accessories commonly worn by a bride on her wedding day. This research aims to identify authentic traditional bridal hair accessories of Great Aceh culture, to identify modified traditional bridal hair accessories worn by the brides from Great Aceh regency, and to find out the cause of the change in bridal hair accessories of Great Aceh brides. The method of analysis used was descriptive qualitative method, and area of research comprised of Great Aceh and Banda Aceh. The subject of this research is 6 people which consists of 3 make up artists, 2 brides, and 1 Acehnese traditional figure. Technique used to conduct data was literature study, interview, observation, and documentation. The results showed that the original types of bridal hair accessories from Great Aceh are lapek patham dhoe, patham dhoe, culok k, priek-priek, ayeum gumbak, and bungong gt-gt. The research also found that there are several types of modified bridal hair accessories worn by Great Aceh brides, among those are crowns, modified priek-priek, modified culok ok, modified kembang goyang, forehead ornaments, and fresh flowers. The change in bridal hair accessories of Great Aceh brides may be caused by the lack of people willing to socialize about the authentic traditional bridal hair accessories of Great Aceh culture, current development that may change peoples preferences and tastes, the rampant growth of new make up artists who dont have enough knowledge about the meaning of each and every piece of the authentic traditional bridal hair accessories of Great Aceh culture, and the declining production of the authentic traditional bridal hair accessories of Great Aceh regency. Keywords: Hair Accessories, Bride.